2017
DOI: 10.1609/aaai.v31i1.10598
|View full text |Cite
|
Sign up to set email alerts
|

Phragmén’s Voting Methods and Justified Representation

Abstract: In the late 19th century, Lars Edvard Phragmén proposed a load-balancing approach for selecting committees based on approval ballots. We consider three committee voting rules resulting from this approach: two optimization variants one minimizing the maximal load and one minimizing the variance of loads —and a sequential variant. We study Phragmén's methods from an axiomatic point of view, focussing on justified representation and related properties that have recently been introduced by Aziz et al. (2015a) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 11 publications
0
43
0
Order By: Relevance
“…This voting rule can be seen as an analogue of the Black rule, which is a single-winner rule that outputs a Condorcet winner if one exists and a Borda winner otherwise. Very recently, Brill et al (2017) identified a voting rule that provides both PR and PJR for all values of n and k, namely, a maximization version of the Phragmén's rule, which they refer to as max-Phragmen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This voting rule can be seen as an analogue of the Black rule, which is a single-winner rule that outputs a Condorcet winner if one exists and a Borda winner otherwise. Very recently, Brill et al (2017) identified a voting rule that provides both PR and PJR for all values of n and k, namely, a maximization version of the Phragmén's rule, which they refer to as max-Phragmen.…”
Section: Discussionmentioning
confidence: 99%
“…It is then natural to ask if there is a polynomial-time computable voting rule that satisfies PJR for all values of n and k. Interestingly, it turns out that the answer to this question is 'yes': in a very recent paper, Brill et al (2017) describe an approval-based multi-winner rule developed by the Swedish mathematician Lars Edvard Phragmén more than 100 years ago, and show that a sequential variant of this rule, which they refer to as seq-Phragmen, is polynomial-time computable and provides PJR. Another voting rule with this combination of properties is the ODH rule, which has been proposed by Sánchez-Fernández, Fernández, and Fisteus in a recent arXiv preprint .…”
Section: Theorem 5 Consider a Ballot Profilementioning
confidence: 99%
“…'s Rules In the late 19th century, Swedish mathematician Lars Edvard Phragmén proposed a load-balancing approach for selecting committees (Phragmén 1894; Janson 2016). Here, we formulate two particularly interesting variants (see Brill et al 2017).…”
Section: Approval-based Multiwinner Election Rulesmentioning
confidence: 99%
“…This model captures a number of applications: the candidates could be potential members of a governing body, items to be shown on a seller's homepage, or tunes to be played at a wedding. Accordingly, there is a number of natural voting rules that take approval ballots as their input and output a set of committees that are tied for winning (Kilgour 2010;Brams and Fishburn 2007;LeGrand, Markakis, and Mehta 2007;Aziz et al 2015;Skowron, Faliszewski, and Lang 2016;Sánchez-Fernández, Fernández, and Fisteus 2016;Brill et al 2017). Many of these voting rules attempt to ensure that all groups of voters are fairly represented in the selected committee.…”
Section: Introductionmentioning
confidence: 99%
“…argued that two well-studied approval-based committee selection rules satisfy PJR when the target committee size k divides the number of voters n; one of these rules is polynomial-time computable. Other authors identified two polynomial-time computable rules that satisfy PJR for all values of k and n (Brill et al 2017;Sánchez-Fernández, Fernández, and Fisteus 2016). However, the complexity of checking whether a given committee provides PJR remained open.…”
Section: Introductionmentioning
confidence: 99%